Review of peridynamics - Ladányi, Gábor (Strojniški vestnik, 2021)
The modelling and simulation of material degradations, particularly fractures in solids of different lengths and time scales, remains challenging despite the numerous approaches that have been developed. In this review, the focus is set on research work concerned with a very promising non-local method: peridynamic modelling. With this approach, continuous phenomena may be described, and the complete evolution (i.e., initiation, propagation, branching, or coalescence) of cracks and other discontinuities can be followed in solids in an integrated framework. Evaluating the large number of publications on this topic, the authors chose to present concisely the key concepts, applications, and results in identifying possible future paths: the incorporation of mechanics of large deformations and material nonlinearities, and the development of high-efficiency peridynamic solvers. This review does not intersect with recent relevant reviews, which reflects its significance to readers.
Keywords: damage mechanics; fracture mechanics; lomna mehanika; mehanika poškodb; nelokalna mehanika; non-local mechanics; peridinamika; peridynamics